Energy management system ISO 50001:2011 and energy management for sustainable development - Gonçalves, Vítor António da Silva (2020)
Starting from sustainable development, energy efficiency and energy management fundamentals, a detailed analysis of the energy management systems standard ISO 50001:2011 was carried out from the viewpoint of sustainable development. The purpose of the analysis was to assess the effectiveness of its implementation, to identify the existence of gaps and to develop improvements capable of fulfilling the identified gaps. The effectiveness and the results of ISO 50001:2011 implementation, combined with the construction of an ideal energy management system allowed the identification of four gaps. The contribution to sustainable development of these gaps was determined. A detailed framework analysis of the four identified gaps followed, reviewing the associated ISO 50001:2011 standard requirements and converting them into six potential improvements. These were then proposed to 146 experts in energy management systems via an on line survey. Experts were divided into three groups, dependent upon their specific areas of expertise, in order to obtain legitimate opinion and validation. The results of this survey, with a global 64.4% positive concordance, showed clear evidence that the six selected improvement proposals, could contribute positively to the evolution of ISO 50001 towards energy management for sustainable development.